Phytoplankton and Water Environment Conditions in the Noe Meto River - Priyambodo, Hernur Yoga; Santiari, Made (Universitas Jember, 2024)
This research aims to determine the structure of the phytoplankton community and the values of chemical and physical water parameters in the Noe Meto river. This research was carried out using purposive sampling by paying attention to sampling stations in places used by local people to wash clothes or motorbikes. A total of 3 research stations had water samples taken to analyze the type of phytoplankton in the laboratory. Meanwhile, environmental factors such as pH and temperature are carried out in situ. The research results showed that the existing phytoplankton community had an abundance value of 6-328 ind/L, a diversity index value of between 1.698-2.200, a uniformity index value of 0.708-0885 and a dominance index value of between 0.128-0.242. All of the phytoplankton species found were from the Bacillariophyceae class. The water temperature values of the Noe Meto River from the three stations range from 29.67oC-31oC and the pH value of the water is 7 or neutral. Based on existing data, it shows that the phytoplankton in the Noe Meto river is experiencing environmental pressure in the moderate category.